Fuzzy Continuous Review Inventory Model using ABC Multi-Criteria Classification Approach: A Single Case Study - Ginting, Meriastuti -; Julita, Julita - (The Asian Journal of Technology Management (AJTM), 2015)
Abstract. Inventory is considered as the most expensive, yet important,to any companies. It representsapproximately 50% of the total investment. Inventory cost has become one of the majorcontributorsto inefficiency, therefore it should be managed effectively. This study aims to propose an alternative inventory model, Ã‚Â by using ABC multi-criteria classification approach to minimize total cost. By combining FANP (Fuzzy Analytical Network Process) and TOPSIS (Technique of Order Preferences by Similarity to the Ideal Solution), the ABC multi-criteria classification approach identified 12 items of 69 inventory items as Ã¢â‚¬Å“outstanding important classÃ¢â‚¬Â that contributed to 80% total inventory cost. This finding Ã‚Â is then used as the basis to determine the proposed continuous review inventory model.This study found that by using fuzzy trapezoidal cost, the inventory Ã‚Â turnover ratio can be increased, and inventory cost can be decreased by 78% for each item in Ã¢â‚¬Å“class AÃ¢â‚¬Â inventory.Keywords:ABC multi-criteria classification, FANP-TOPSIS, continuous review inventory model lead-time demand distribution, trapezoidal fuzzy numberÃ‚Â